Using Guided Reading to Enhance Reading Comprehension among Junior High Students During Online Learning - Siswoyo Siswoyo (EXPOSE (Journal of English Education and for Specific Purpose), 2024)
This study aims to analyze the effectiveness of implementing the Guided Reading technique in enhancing reading comprehension among eighth-grade students at SMP Negeri 2 Lampung during online learning amid the COVID-19 pandemic. The research method employed is Classroom Action Research (CAR), conducted over two cycles with a total of 44 eighth-grade students as participants. Data collection involved reading comprehension tests, observations of learning activities, and student response questionnaires concerning the learning process. The findings reveal a significant improvement, with the average pre-cycle score of 60.11 increasing to 73.41 in the first cycle, and further rising to 83.52 in the second cycle. This progress can be attributed to Guided Reading's provision of structured guidance, which facilitates students' understanding of texts through guiding questions, vocabulary reinforcement, and targeted discussions. These results suggest that Guided Reading is an effective, straightforward, and flexible strategy for supporting online reading instruction. Furthermore, this research contributes substantially to the existing literature by confirming the relevance of the Guided Reading strategy in the context of remote learning at the middle school level.